Daily self-compassion protects Asian Americans/Canadians after experiences of COVID-19 discrimination: Implications for subjective well-being and health behaviors. Issue 8 (17th November 2022) - Zhang, Jia Wei; Bui, van; Snell, Andrew N.; Howell, Ryan T.; Bailis, Dan
ABSTRACT: Asians are not immune to racial discrimination and discrimination against Asians has heightened during the COVID-19 pandemic because they were blamed as the origin of the virus. A pre-registered 14-day diary explored if self-compassion was associated with subjective well-being and protective behaviors for Asians (U.S. & Canada) who faced COVID-19 discriminations (N = 82 & ndiaries =711). Participants reported discriminations experience for 28% (U.S.) and 25% (Canada) of their days. Daily self-compassion predicted daily subjective well-being despite COVID-19 discrimination experience. Daily self-compassion predicted increased COVID-19 protective behaviors on days Asian Americans experienced COVID-19 discrimination. Daily acceptance, but not daily reappraisal, explained the link between daily self-compassion and daily subjective well-being. These findings could not be accounted for by daily self-esteem.